Forró Imre (1910–1985) franekeri kutatása - Bozzay, Réka (Studia Litteraria, 2026)
Imre Forró began researching the studies of Hungarian students in Franeker in 1932 as a Stipendium Bernardinum scholarship holder. Upon returning to Hungary, his work was accused of plagiarism, a claim that was later proven to be unfounded. Nevertheless, the controversy led him to set his work aside for decades. In 1954, the De Wever Publishing House in Friesland showed interest in Forró’s manuscript, which was also considered by the journal Egyháztörténet in Hungary. Forró applied for the Stipendium Bernardinum scholarship again in 1960, which he was awarded in the spring of that year. After a long delay, he was finally able to travel in 1964. While he was waiting for his permission, he focused on gathering relevant literature on Franeker. Aer returning to Hungary, he organized his manuscript with the help of Pieter Tuinhof. Despite receiving full support from the Fryske Akademy and preparing the manuscript for publication, Forró felt it lacked readability and decided to write an extended introduction. Ultimately, the manuscript was never published, and only the introduction was released posthumously by his family.